Theft and taxes☆ - DESAI, M; DYCK, A; ZINGALES, L (Journal of Financial Economics, 2007)
This paper analyzes the interaction between corporate taxes and corporate governance. We show that the design of the corporate tax system affects the amount of private benefits extracted by company insiders and that the quality of the corporate governance system affects the sensitivity of tax revenues to tax changes. Analyses of a tax enforcement crackdown in Russia and cross-country data on tax changes support this two-way interaction between corporate governance and corporate taxation.